THE ROLE OF FINANCIAL LEVERAGE IN PREDICTING EARNINGS PER SHARE: A PANEL DATA APPROACH - Muhammad Al Faridho Awwal (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study aims to analyze the role of financial leverage in predicting earnings per share (EPS) using a panel data approach. Leverage is measured using the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), while EPS is used as the main indicator of the company's profitability performance. The research sample consists of non-financial sector companies listed on the Indonesia Stock Exchange during the period 2018–2023, selected using purposive sampling technique. The analysis method used is panel data regression with the Fixed Effect Model (FEM) approach, which was chosen based on the results of the Hausman test. The research results indicate that leverage has a negative and significant impact on EPS, which suggests that excessive use of debt can reduce earnings per share due to high interest expenses. These findings have important implications for company management in optimally managing capital structure and for investors in assessing the company's financial risk.